Evidence-Based Mind-Body Interventions for Children and Adolescents with Functional Neurological Disorder. Issue 2 (March 2023) - Kozlowska, Kasia; Chudleigh, Catherine; Savage, Blanche; Hawkes, Clare; Scher, Stephen; Nunn, Kenneth P.
Abstract : Learning objectives: Develop and implement treatment plans for children and adolescents with functional neurological disorder (FND) Outline a plan to increase awareness and standardize the care for patients with FND using evidence-based interventions Abstract: Functional neurological disorder (FND) in children and adolescents involves the biological embedding of lived experience in the body and brain. This embedding culminates in stress-system activation or dysregulation and in aberrant changes in neural network function. In pediatric neurology clinics, FND represents up to one-fifth of patients. Current research shows good outcomes with prompt diagnosis and treatment using a biopsychosocial, stepped-care approach. At present, however—and worldwide—FND services are scarce, the result of long-standing stigma and ingrained belief that patients with FND do not suffer from a real ("organic") disorder and that they therefore do not require, or even deserve, treatment. Since 1994, the Mind-Body Program for children and adolescents with FND at The Children's Hospital at Westmead in Sydney, Australia—run by a consultation-liaison team—has delivered inpatient care to hundreds of patients with FND and outpatient care to hundreds of others. For less-disabled patients, the program enables community-based clinicians to implement biopsychosocial interventions locally by providing a positive diagnosis (by a neurologist or pediatrician), a biopsychosocial assessment and formulation (by clinicians from the consultation-liaison team), a physical therapy assessment, and clinical support (from the consultation-liaison team and the physiotherapist). In this Perspective we describe the elements of a biopsychosocial mind-body program intervention capable of providing, as needed, effective treatment to children and adolescents with FND. Our aim is to communicate to clinicians and institutions around the world what is needed to establish effective community treatment programs, as well as hospital inpatient and outpatient interventions, in their own health care settings.